Mechanical characteristics of coal under differential cyclic loading after dry-wet cyclic treatment - LIU Huafeng (Gong-kuang zidonghua)
In underground coal mine reservoirs, coal pillar dams are subjected to dynamic dry-wet environmental disturbances. Studying the mechanical characteristics of coal solely under dry-wet cycling or cyclic loading and unloading conditions is not comprehensive or objective enough. To address this problem, the mechanical characteristics of coal samples after dry-wet cyclic treatment under differential cyclic loading were studied experimentally. Coal samples were divided into four groups for testing: Group 1 was in a natural state, Group 2 underwent 10 dry-wet cycles, Group 3 underwent 40 dry-wet cycles, and Group 4 was continuously soaked in water. Two test modes were designed: Mode 1 featured rapid loading and slow unloading, while Mode 2 involved slow loading and rapid unloading. The evolution trend of strain, secant modulus, and Poisson′s ratio of coal samples with the number of cycles was analyzed. Results revealed that the loading mode significantly affected the mechanical properties of coal samples. Peak and residual strains of coal samples under Mode 1 were higher than those under Mode 2. Coal samples without damage during the entire cyclic loading phase exhibited greater secant modulus increments under Mode 1. Poisson′s ratio increased gradually during the initial loading cycles but rose sharply in the last two or pre-failure cycles. The Poisson′s ratio increment of coal samples after dry-wet cycling was higher than those in natural state. These findings can provide safety guidance for the stability design of coal pillar dams in underground reservoirs, aiming to enhance their stability and safety.